Political Rhetoric in the Digital Age: A Linguistic Analysis of Persuasion and Power - Khashan, Mudhafar Saiwan (International Consortium of Education and Culture Research Studies, 2025)
General Background Digital media have reconfigured how political communication operates, reshaping the linguistic practices that structure persuasion and power. Specific Background Traditional rhetorical strategies rooted in logos, ethos, and pathos now intersect with the speed, interactivity, and multimodality of online platforms. Knowledge Gap Despite extensive scholarship on classical rhetoric, less is known about how political actors linguistically adapt persuasive strategies within rapidly evolving digital environments. Aims This study examines contemporary political rhetoric by analyzing large corpora of social-media posts and speeches to identify the rhetorical mechanisms politicians use to construct authority, influence audiences, and negotiate power. Results The findings indicate substantial shifts in political discourse, marked by increased personalization, hybrid oral–digital delivery, and intensified reliance on authority appeals, emotional framing, and strategic identity construction. Quantitative patterns reveal differentiated agency across platforms, while qualitative cases show how digital affordances reshape rhetorical efficacy. Novelty The study integrates large-scale corpus analysis with rhetorical theory to provide an empirically grounded account of how digital communication restructures persuasive political language. Implications These insights underscore the need to reconceptualize political rhetoric within a multiscalar digital framework, highlighting how evolving communicative ecologies reshape public discourse, political influence, and democratic engagement.Highlight : Highlights shifts in political rhetoric within digital spaces. Describes linguistic strategies used to strengthen persuasion. Explains how digital media reshape political communication. Keywords : Political Rhetoric, Digital Age, Linguistic Analysis, Persuasion, Power